"Snowed Up" : le topos montagnard dans Women in Love de D. H. Lawrence - Philippe Birgy (Anglophonia)
Throughout the 18th and 19th centuries, the mountain gradually crystallised into an overdetermined topos. From then on, it could not be separated from the complex of perceptive, affective and intellectual prescriptions dictating the modalities of its textualization. Understandably, Modernism was at pains to accommodate this topos in its literary programme. Women in Love, insofar as it can be defined as a modernist text—a whole problem in itself—struggles with the implications of a transcendence and more generally with the whole tradition of metaphysics. This article proposes to consider the influence of this "hypertextual mountain" on the last two chapters of the novel and to observe how it shapes and at the same time undermines the literary discourse of Lawrence